WOMEN’S EMPOWERMENT IN MONA LISA SMILE MOVIE SCRIPT - Tessalonika Venesa Machmud; Imelda Lolowang; Fivy Andries (Program Studi Pendidikan Bahasa Inggris, 2023)
The purpose of this research is to describe women's empowerment in Mona Lisa Smile Movie Script. This research is a qualitative research because the data in the form of words. In analyzing the data will be used, Napikoski’s feminist literary theory. The data were collected from the main source of the movie script itself in this case Mona Lisa Smile Movie Script, and the secondary sources were several books, journals, web pages and other references used to support this research. The results showed that empowering women on these days are important. The movie reflects the women conditions at the time that still hold the tradition controlled by patriarchal where gender roles dictated that men were the head of the household and the sole provider, while women were expected to be the homemaker who cared for the family. Being a mother and a wife were viewed as women’s most critical callings. Katherine made the students realize that they had rights to show up their capability in public as men had. Katherine caused her understudies to accept that they could complete two things in a similar time; having family and their goal as well. Empowering women is the key to political stability, economic growth and social transformation.